Mississippi missionaries' workplace spirituality and organizational commitment (1698-1725): a case study - Jones, Linda C. (Journal of management, spirituality & religion, 2016)
The relationship between workplace spirituality and organizational commitment in modern settings is often examined using models focused on personal and organizational performance. Meant for contemporary practices, such tools can enhance understanding of organizations in the historic record, benefiting not only historians but researchers who wish to ameliorate commitment in organizations. Utilizing a recent model focused on workplace spirituality and organizational commitment, this study examines the leadership of the Séminaire de Québec and the Séminaire des Missions Etrangères de Paris as well as their secular missionaries assigned to work in villages on the Mississippi River in the early eighteenth century. Analyses demonstrate that the inability to maintain communication, support, and community between leadership and missionaries greatly hampered commitment to the organization and to the Mississippi missions. Only Father Bergier remained strongly committed to his work and the Seminaries due to his personal sense of calling, devotion, leadership, and spirituality.